Auto‐Oxidative Povarov/Aromatization Tandem Reaction of Glycine Derivatives with Enamides: Acylamino as both Activating and Leaving Group. Issue 6 (18th May 2020) - Huang, Songhai; Bao, Xiazhen; Fu, Ying; Zhang, Yongxin; Quan, Zhengjun; Huo, Congde
Abstract: The auto‐oxidative Povarov/aromatization tandem reaction of N‐aryl glycine derivatives with enamides yields a series of complex quinoline derivatives in good yields. The reactions are performed using only catalytic amount of Brønsted acid and O2 . The acylamino group is used as both activating and leaving group to improve the reaction efficiency in this transformation. Abstract : Cyclization : Auto‐oxidative Povarov/aromatization tandem reaction of N‐aryl glycine derivatives with enamides yields a series of complex quinoline derivatives in good yields. The reactions are performed using only catalytic amount of Brønsted acid and O2 . The acylamino group is used as both activating and leaving group to improve the reaction efficiency in this transformation